The Shono-type electroorganic oxidation of unfunctionalised amides. Carbon–carbon bond formation via electrogenerated N-acyliminium ions - Jones, Alan M.; Banks, Craig E. (Beilstein Journal of Organic Chemistry, 2014)
N-acyliminium ions are useful reactive synthetic intermediates in a variety of important carbon–carbon bond forming and cyclisation strategies in organic chemistry. The advent of an electrochemical anodic oxidation of unfunctionalised amides, more commonly known as the Shono oxidation, has provided a complementary route to the C–H activation of low reactivity intermediates. In this article, containing over 100 references, we highlight the development of the Shono-type oxidations from the original direct electrolysis methods, to the use of electroauxiliaries before arriving at indirect electrolysis methodologies. We also highlight new technologies and techniques applied to this area of electrosynthesis. We conclude with the use of this electrosynthetic approach to challenging syntheses of natural products and other complex structures for biological evaluation discussing recent technological developments in electroorganic techniques and future directions.
Keywords: anodic oxidation; electrochemistry; electroorganic, electrosynthesis, N-acyliminium ions; natural products; non-Kolbe oxidation; peptidomimetics; Shono oxidation; synthesis

(untitled) - Mayr, H.; Ofial, A. R.; Würthwein, E.-U.; Aust, N. C. (J. Am. Chem. Soc., 1997)

(untitled) - Yamamoto, Y.; Nakada, T.; Nemoto, H. (J. Am. Chem. Soc., 1992)

(untitled) - Speckamp, W. N.; Hiemstra, H. (Tetrahedron, 1985)

(untitled) - Royer, J.; Bonin, M.; Micouin, L. (Chem. Rev., 2004)

(untitled) - Yoshida, J.-i.; Kataoaka, K.; Horcajada, R.; Nagaki, A. (Chem. Rev., 2008)

(untitled) - Sperry, J. B.; Wright, D. L. (Chem. Soc. Rev., 2006)

(untitled) - Francke, R.; Little, R. D. (Chem. Soc. Rev., 2014)

(untitled) - Utley, J. (Chem. Soc. Rev., 1997)

(untitled) - Frontana-Uribe, B. A.; Little, R. D.; Ibanez, J. G.; Palma, A.; Vaquez-Medrano, R. (Green Chem., 2010)

(untitled) - Shono, T. (Tetrahedron, 1984)

(untitled) - Shono, T.; Matsumura, Y.; Tsubata, K. (J. Am. Chem. Soc., 1981)

(untitled) - Ross, S. D.; Finkelstein, M.; Peterson, R. C. (J. Am. Chem. Soc., 1966)

(untitled) - Shono, T.; Hamaguchi, H.; Matsumura, Y. (J. Am. Chem. Soc., 1975)

(untitled) - Shono, T.; Matsumura, Y.; Tsubata, K. (Org. Synth., 1985)

(untitled) - Nyberg, K.; Servin, R. (Acta Chem. Scand., Ser. B, 1976)

(untitled) - Libendi, S. S.; Demizu, Y.; Matsumura, Y.; Onomura, O. (Tetrahedron, 2008)

(untitled) - Suga, S.; Okajima, M.; Yoshida, J.-i. (Tetrahedron Lett., 2001)

(untitled) - Suga, S.; Kageyama, Y.; Babu, G.; Itami, K.; Yoshida, J.-i. (Org. Lett., 2004)

(untitled) - Maruyama, T.; Suga, S.; Yoshida, J.-i. (Tetrahedron, 2006)

(untitled) - Kirira, P. G.; Kuriyama, M.; Onomura, O. (Chem. – Eur. J., 2010)

(untitled) - Suga, S.; Tsutsui, Y.; Nagaki, A.; Yoshida, J.-i. (Bull. Chem. Soc. Jpn., 2005)

(untitled) - Suga, S.; Nishida, T.; Yamada, D.; Nagaki, A.; Yoshida, J.-i. (J. Am. Chem. Soc., 2004)

(untitled) - Suga, S.; Nagaki, A.; Tsutsui, Y.; Yoshida, J.-i. (Org. Lett., 2003)

(untitled) - Suga, S.; Suzuki, S.; Maruyama, T.; Yoshida, J.-i. (Bull. Chem. Soc. Jpn., 2004)

(untitled) - Suga, S.; Suzuki, S.; Yoshida, J.-i. (J. Am. Chem. Soc., 2002)

(untitled) - Suga, S.; Okajima, M.; Fujiwara, K.; Yoshida, J.-i. (J. Am. Chem. Soc., 2001)

(untitled) - Maruyama, T.; Mizuno, Y.; Shimizu, I.; Suga, S.; Yoshida, J.-i. (J. Am. Chem. Soc., 2007)

(untitled) - Maruyama, T.; Suga, S.; Yoshida, J.-i. (J. Am. Chem. Soc., 2005)

(untitled) - Nagaki, A.; Kawamura, K.; Suga, S.; Ando, T.; Sawamoto, M.; Yoshida, J.-i. (J. Am. Chem. Soc., 2004)

(untitled) - Suga, S.; Okajima, M.; Fujiwara, K.; Yoshida, J.-i. (QSAR Comb. Sci., 2005)

(untitled) - Yoshida, J.-i.; Suga, S.; Suzuki, S.; Kinomura, N.; Yamamoto, A.; Fujiwara, K. (J. Am. Chem. Soc., 1999)

(untitled) - Sugawara, M.; Mori, K.; Yoshida, J.-i. (Electrochim. Acta, 1997)

(untitled) - Kim, S.; Hayashi, K.; Kitano, Y.; Tada, M.; Chiba, K. (Org. Lett., 2002)

(untitled) - Yoshida, J.-i.; Isoe, S. (Tetrahedron Lett., 1987)

(untitled) - Le Gall, E.; Hurvois, J.-P.; Sinbandhit, S. (Eur. J. Org. Chem., 1999)

(untitled) - Fuchigami, T.; Tetsu, M.; Tajima, T.; Ishii, H. (Synlett, 2001)

(untitled) - Cao, Y.; Suzuki, K.; Tajima, T.; Fuchigami, T. (Tetrahedron, 2005)

(untitled) - Horii, D.; Fuchigami, T.; Atobe, M. (J. Am. Chem. Soc., 2007)

(untitled) - Horii, D.; Amemiya, F.; Fuchigami, T.; Atobe, M. (Chem. – Eur. J., 2008)

(untitled) - Kuleshova, J.; Hill-Cousins, J. T.; Birkin, P. R.; Brown, R. C. D.; Pletcher, D.; Underwood, T. J. (Electrochim. Acta, 2012)

(untitled) - Horcajada, R.; Okajima, M.; Suga, S.; Yoshida, J.-i. (Chem. Commun., 2005)

(untitled) - Hayashi, K.; Kim, S.; Chiba, K. (Electrochemistry, 2006)

(untitled) - Suga, S.; Nagaki, A.; Yoshida, J.-i. (Chem. Commun., 2003)

(untitled) - Nagaki, A.; Togai, M.; Suga, S.; Aoki, N.; Mae, K.; Yoshida, J.-i. (J. Am. Chem. Soc., 2005)

(untitled) - Asami, R.; Fuchigami, T.; Atobe, M. (Chem. Commun., 2008)

(untitled) - Asami, R.; Fuchigami, T.; Atobe, M. (Org. Biomol. Chem., 2008)

(untitled) - Tajima, T.; Fuchigami, T. (Chem. – Eur. J., 2005)

(untitled) - Tajima, T.; Fuchigami, T. (J. Am. Chem. Soc., 2005)

(untitled) - Tajima, T.; Kurihara, H.; Fuchigami, T. (J. Am. Chem. Soc., 2007)

(untitled) - Tajima, T.; Fuchigami, T. (Angew. Chem., Int. Ed., 2005)

(untitled) - Tajima, T.; Nakajima, A. (Chem. Lett., 2009)

(untitled) - Nad, S.; Breinbauer, R. (Angew. Chem., Int. Ed., 2004)

(untitled) - Tajima, T.; Nakajima, A. (J. Am. Chem. Soc., 2008)

(untitled) - Bornemann, S.; Handy, S. T. (Molecules, 2011)

(untitled) - Nguyen, B. H.; Redden, A.; Moeller, K. D. (Green Chem., 2014)

(untitled) - Siu, T.; Li, W.; Yudin, A. K. (J. Comb. Chem., 2000)

WO Pat. Appl. - Reufer, C.; Lehmann, T.; Sanzenbacher, R.; Weckbecker, C. (Verfahren zur anodischen alkoxylierung von organischen substraten, 2004)

(untitled) - Shiigi, H.; Mori, H.; Tanaka, T.; Demizu, Y.; Onomura, O. (Tetrahedron Lett., 2008)

(untitled) - Demizu, Y.; Shiigi, H.; Oda, T.; Matsumura, Y.; Onomura, O. (Tetrahedron Lett., 2008)

(untitled) - Adamek, J.; Mazurkiewicz, R.; Październiok-Holewa, A.; Grymel, M.; Kuźnik, A.; Zielińska, K. (J. Org. Chem., 2014)

(untitled) - Izawa, K.; Nishi, S.; Asada, S. (J. Mol. Catal., 1987)

(untitled) - Myers, E. L.; de Vries, J. G.; Aggarawal, V. K. (Angew. Chem., Int. Ed., 2007)

(untitled) - Vink, M. K. S.; Schortinghuis, C. A.; Luten, J.; van Maarseveen, J. H.; Schoemaker, H. E.; Hiemstra, H.; Rutjes, F. P. J. T. (J. Org. Chem., 2002)

(untitled) - Bartels, M.; Zapico, J.; Gallagher, T. (Synlett, 2004)

(untitled) - David, M.; Dhimane, H. (Synlett, 2004)

(untitled) - Golub, T.; Becker, J. Y. (J. Electrochem. Soc., 2013)

(untitled) - Suda, K.; Hotoda, K.; Iemuro, F.; Takanami, T. (J. Chem. Soc., Perkin Trans. 1, 1993)

(untitled) - Suda, K.; Hotoda, K.; Watanabe, J.-i.; Shiozawa, K.; Takanami, T. (J. Chem. Soc., Perkin Trans. 1, 1992)

(untitled) - D’Oca, M. G. M.; Pilli, R. A.; Pardini, V. L.; Curi, D.; Comninos, F. C. M. (J. Braz. Chem. Soc., 2001)

(untitled) - Turcaud, S.; Martens, T.; Sierecki, E.; Pérard-Viret, J.; Royer, J. (Tetrahedron Lett., 2005)

(untitled) - Shankaraiah, N.; Pilli, R. A.; Santos, L. S. (Tetrahedron Lett., 2008)

(untitled) - Kanda, Y.; Onomura, O.; Maki, T.; Matsumura, Y. (Chirality, 2003)

(untitled) - Lennartz, M.; Steckhan, E. (Synlett, 2000)

(untitled) - Lee, D.-S. (Tetrahedron: Asymmetry, 2009)

(untitled) - Moore, J. C.; Davies, E. S.; Walsh, D. A.; Sharma, P.; Moses, J. E. (Chem. Commun., 2014)

(untitled) - Suga, S.; Watanabe, M.; Yoshida, J.-i. (J. Am. Chem. Soc., 2002)

(untitled) - Suga, S.; Watanabe, M.; Song, C.-H.; Yoshida, J.-i. (Electrochemistry, 2006)

(untitled) - Vu, V. H.; Louafi, F.; Girard, N.; Marion, R.; Roisnel, T.; Dorcet, V.; Hurvois, J.-P. (J. Org. Chem., 2014)

(untitled) - Wong, P. L.; Moeller, K. D. (J. Am. Chem. Soc., 1993)

(untitled) - Wang, X.; Li, J.; Saporito, R. A.; Toyooka, N. (Tetrahedron, 2013)

(untitled) - Moriyama, N.; Matsumura, Y.; Kuriyama, M.; Onomura, O. (Tetrahedron: Asymmetry, 2009)

(untitled) - Furukubo, S.; Moriyama, N.; Onomura, O.; Matsumura, Y. (Tetrahedron Lett., 2004)

(untitled) - Faust, M. R.; Höfner, G.; Pabel, J.; Wanner, K. T. (Eur. J. Med. Chem., 2010)

(untitled) - Saka, T.; Okaki, T.; Ifuku, S.; Yamashita, Y.; Sato, K.; Miyawaki, S.; Kamori, A.; Kato, A.; Adachi, I.; Tezuka, Y.; Kiria, P. G.; Onomura, O.; et al. (Tetrahedron, 2013)

(untitled) - Kato, A.; Okaki, T.; Ifuku, S.; Sato, K.; Hirokami, Y.; Iwaki, R.; Kamori, A.; Nakagawa, S.; Adachi, I.; Kiria, P. G.; Onomura, O.; Minato, D.; et al. (Bioorg. Med. Chem., 2013)

(untitled) - Dooms, C.; Laurent, P.; Daloze, D.; Pasteels, J.; Nedved, O.; Braekman, J.-C. (Eur. J. Org. Chem., 2005)

(untitled) - Sunilkumar, G.; Nagamani, D.; Argade, N. P.; Ganesh, K. N. (Synthesis, 2003)

(untitled) - Kim, S.; Shoji, T.; Kitano, Y.; Chiba, K. (Chem. Commun., 2013)

(untitled) - Hack, V.; Reuter, C.; Opitz, R.; Schmieder, P.; Beyermann, M.; Neudörfl, J.-M.; Kühne, R.; Schmalz, H.-G. (Angew. Chem., Int. Ed., 2013)

(untitled) - Reuter, C.; Huy, P.; Neudörfl, J.-M.; Kühne, R.; Schmalz, H.-G. (Chem. – Eur. J., 2011)

(untitled) - Sun, H.; Moeller, K. D. (Org. Lett., 2002)

(untitled) - Sun, H.; Martin, C.; Kesselring, D.; Keller, R.; Moeller, K. D. (J. Am. Chem. Soc., 2006)

(untitled) - Tong, Y.; Fobian, Y. M.; Wu, M.; Boyd, N. D.; Moeller, K. D. (J. Org. Chem., 2000)

(untitled) - Slomczynska, U.; Chalmers, D. K.; Cornille, F.; Smythe, M. L.; Beusen, D. D.; Moeller, K. D.; Marshall, G. R. (J. Org. Chem., 1996)

(untitled) - Cornille, F.; Slomczynska, U.; Smythe, M. L.; Beusen, D. D.; Moeller, K. D.; Marshall, G. R. (J. Am. Chem. Soc., 1995)

(untitled) - Le Corre, L.; Kizirian, J.-C.; Levraud, C.; Boucher, J.-L.; Bonnet, V.; Dhimane, H. (Org. Biomol. Chem., 2008)

(untitled) - Le Corre, L.; Dhimane, H. (Tetrahedron Lett., 2005)

(untitled) - Gorewoda, T.; Mazurkiewicz, R.; Simka, W.; Mlostoń, G.; Schroeder, G.; Kubicki, M.; Kuźnik, N. (Tetrahedron: Asymmetry, 2011)

(untitled) - Kardassis, G.; Brungs, P.; Steckhan, E. (Tetrahedron, 1998)

(untitled) - Kardassis, G.; Brungs, P.; Nothhelfer, C.; Steckhan, E. (Tetrahedron, 1998)

(untitled) - Kabeshov, M. A.; Musio, B.; Murray, P. R. D.; Browne, D. L.; Ley, S. V. (Org. Lett., 2014)